THE INFLUENCE OF AUDIT QUALITY, GOOD CORPORATE GOVERNANCE AND LIQUIDITY ON OPINION AUDIT GOING CONCERN CONSUMPTION GOODS COMPANIES REGISTERED ON THE IDX YEAR 2019-2021 - Enda Noviyanti Simorangkir; Darwin Wijaya; Felixcyrus Ganily; Angelina; Putri Wahyuni (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Audit quality, good corporate leadership, and liquidity are factors influencing the acceptance of a concerned audit opinion. In this capital market, both large companies and small companies are listed. Companies large and small alike have assets. Large companies usually have more access than small companies. Large companies often get going concern audit opinions because of the ease of obtaining funds. This study aims to evaluate the effect of company size, audit quality, good company management, and liquidity on the concern audit opinions of consumer goods companies listed on the Indonesia Stock Exchange between 2019 and 2021.Financial report data is the source of data used in this study. This. This study analyzes consumer goods companies Registered on the Indonesia Stock Exchange from 2019 to 2021. During the 2019–2021 research period, a purposive sampling technique was used to select 61 companies. The results of the study show that the Audit Opinion of Going Concern Consumer Goods Companies Registered on the IDX for 2019-2021 is not affected by Audit Quality, Good Corporate Governance, and Liquidity. Data analysis was performed by logistic regression analysis in SPSS.